2000
DOI: 10.1016/s0165-7836(99)00096-x
|View full text |Cite
|
Sign up to set email alerts
|

Response of individual shoaling Atlantic cod to ocean currents on the northeast Newfoundland Shelf

Abstract: The movements of sonically-tagged Atlantic cod swimming within a large (80,000 mt) shoal of post-spawning ®sh on the northeast Newfoundland Shelf were related to the acoustically determined position of the shoal and event structure in the local ocean currents. For the ®rst several days of the study, a period when currents were unfavorable for shoreward transport, the tagged ®sh maintained station. There was little net movement of individual ®sh and no change in the geographical location of the shoal. Then, app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…However, any movement with prevailing currents is more likely to be a result of active rather than passive transport. Observations of the selective use of currents by migrating cod (Arnold et al, 1994;Rose et al, 1995;Wroblewski et al, 2000), as well as observed migrations of postspawning cod moving against the prevailing currents in Placentia Bay (Lawson and Rose, 2000) support this claim. It is unclear how prevailing currents may provide directional clues to homing cod.…”
Section: Resultsmentioning
confidence: 78%
“…However, any movement with prevailing currents is more likely to be a result of active rather than passive transport. Observations of the selective use of currents by migrating cod (Arnold et al, 1994;Rose et al, 1995;Wroblewski et al, 2000), as well as observed migrations of postspawning cod moving against the prevailing currents in Placentia Bay (Lawson and Rose, 2000) support this claim. It is unclear how prevailing currents may provide directional clues to homing cod.…”
Section: Resultsmentioning
confidence: 78%
“…A miniature electronic pinger is placed subcutaneously or in the abdominal cavity of an individual animal. Hydrophones are then used to track the animal’s horizontal and vertical movements (Arnold and Greer Walker, 1992; Wroblewski et al ., 1994, 2000). Tags transmit at specific frequencies to provide a unique marker for each individual.…”
Section: Approaches and Technologies Used To Identify Targetsmentioning
confidence: 99%
“…Tracking of fish in the sea was investigated to locating movement of fish such as flat fish 1,2,3,4), cod 5,6,7,8), saithe 9) and mackerel 10,11) etc.…”
Section: Introductionmentioning
confidence: 99%